2019
DOI: 10.1088/1742-6596/1240/1/012105
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the effect of electroplating and filler material on the tensile properties of wollastonite reinforced ABS composites

Abstract: This paper deals with effects of wt. % of wollastonite (CaSiO3) filler in acrylonitrile-butadiene-styrene (ABS) polymers prepared by injection moulding process and electroplating on the specimens. The influence of filler was examined by the different wt. % (3, 5 and 7) of wollastonite (CaSiO3) in ABS. Filler was mixed with ABS polymer by twin screw extrusion process and pelletized. The composite pellets are used for the injection moulding process and specimens are prepared as per ASTM. The specimens are coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The UTS values range from 21.3 to 36.8 MPa. Chandra et al [51] indicated that the UTS value of ABS is 32.76 MPa, which is close to the values found in this study. At the same time, Singh et al [52] reported that the 3D-printed ABS/HIPS samples achieved a UTS value of 9.9-31.9 MPa.…”
Section: Tensile Test and Taguchi Analysis For Abs/tpu Blendssupporting
confidence: 91%
“…The UTS values range from 21.3 to 36.8 MPa. Chandra et al [51] indicated that the UTS value of ABS is 32.76 MPa, which is close to the values found in this study. At the same time, Singh et al [52] reported that the 3D-printed ABS/HIPS samples achieved a UTS value of 9.9-31.9 MPa.…”
Section: Tensile Test and Taguchi Analysis For Abs/tpu Blendssupporting
confidence: 91%
“…As shown in Figure g, the Gc of PAA–GAs@LMPs is 38.69 KJ m –2 , which is 17.67 and 58.62 times than that of PAA–GAs and PAA, illustrating the satisfactory antitearing ability. Such composites can achieve a balance of tensile strength and elongation, exceeding those of most general-purpose plastics frequently used in daily life (Figure S17), and the toughness is about 3.5 times than that of metallic aluminum …”
Section: Resultsmentioning
confidence: 99%